Productivity Differences in the European Union : National, Regional and Spatial Effects - Kurt Geppert; Martin Gornig; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Using panel data on European regions and applying Analysis of Covariance, our study provides an empirical assessment of the relative importance of national, regional and spatial factors for explaining variations of productivity. Our analysis shows that initial economic conditions or agglomeration and centrality are indeed relevant for differences in productivity levels. What is far more important, however, is which country a region belongs to. Productivity differences in the European Union are thus obviously dominated by national regimes. In light of the historically strong influence of the nation states, this result may come as no surprise. What is surprising is the fact that the role of countries has not decreased over time, despite intensive integration efforts (European Single Market, Economic and Monetary Union).
Keywords: C33; O47; R11; 330; Regional productivity; agglomeration and centrality; panel data econometrics; Produktivität; Regionale Disparität; Kern-Peripherie-Beziehung; Nationalstaat; Schätzung; EU-Staaten